Expression of Sox10 gene during human development - Wegner, Michael; et al. (Febs Letters, 1998)
SOX10, a new member of the SOX gene family, is a transcription factor defective in the Dom (Dominant megacolon) mouse and in the human Shah-Waardenburg syndrome. To help unravel its physiological role during human development, we studied SOX10 gene expression in embryonic, fetal, and adult human tissues by Northern blot and in situ hybridization. As in mice, the human SOX10 gene was essentially expressed in the neural crest derivatives that contribute to the formation of the peripheral nervous system, and in the adult central nervous system. Nevertheless, it was more widely expressed in humans than in rodents. The spatial and temporal pattern of SOX10 expression supports an important function in neural crest development. Copyright (C) 1998 Federation of European Biochemical Societies.
UnivIS-Import:2015-03-05:Pub.1998.med.IB.LPCIPDBI.expres_83
Keywords: Human; In situ hybridization; Neural crest; Northern blot; SOX10